The The use of activated charcoal from corn cobs as adsorbent of heavy metals from groundwater - Ermadani; Viviani, Amalia; Yasdi; Yanopa, Shally; Suryanto; Arsyad; Ar; Sarman (Revista Brasileira de Engenharia de Biossistemas, 2023)
Iron (Fe) and manganese (Mn) are heavy metals which are found in high concentration in highly weathered soils, especially in the tropics, resulting in high content of them in groundwater. These metals cause a distinctive odor, reddish brown, yellowish color, and high sediment. This condition could cause health problems when it is used as a source of drinking water. This study was aimed to evaluate the efficiency of activated carbon from corn cobs in reducing the concentrations of Fe and Mn from groundwater adsorption. The adsorption process was performed by applying activated carbon with varying doses of 0.1 g, 0.2 g, 0.3 g, 0.4 g, 0.5 g, 1 g, 1.5 g and 2 g into 100 ml groundwater. Variations of pH were pH 2, pH 3, pH 4, pH 5, pH 6, pH 7 and pH 8, and variations in contact time of 10, 30, 45, 60, 90 and 120 minutes. The results showed that the optimum doses to reduce Fe and Mn concentration from groundwater were 1 g and 0.5 g with the adsorption efficiency of 70.14% and 41.60% respectively. The optimum pH for both Fe and Mn was pH 4 with an adsorption efficiency of 75.44% and 56.52% respectively, while the optimum contact times were 60 and 30 minutes with an adsorption efficiency of 75.44 dan 59.29% respectively.